Immunosuppressive drugs affect induction of IFNy+ Treg in vitro - Daniel, Volker; Trojan, Karina; Opelz, Gerhard (Human immunology, 2016)
Background - We reported previously that patients with poor long-term graft function are able to form IFNy+ Treg in vitro pretransplant, but late posttransplant have more frequently undetectable or lower levels of IFNy+ Treg in the peripheral blood than patients with good long-term graft outcome. In the present study, we investigated the induction of IFNy+ and Tbet+ Treg subsets in the presence of immunosuppressants in vitro. - Methods - PBL of 10 healthy individuals were stimulated with PMA/Ionomycin in the presence of different immunosuppressive drugs at 2 different concentrations that were chosen to approximately mirror the blood levels in renal transplant recipients. IFNy+, Tbet+, CD119+, and Helios+ CD4+CD25+CD127−Foxp3+ Treg subsets were analyzed using 8-color-fluorescence-flow-cytometry. - Results - Cyclosporine (p<0.01) and 6α-methylprednisolone (p<0.05) at both concentrations as well as high doses of azathioprine (p<0.05) and mycophenolate mofetil (p<0.05) inhibited the induction of IFNy+ and Tbet+ Treg, whereas lower concentrations of azathioprine and mycophenolate mofetil tended to increase IFNy+, Tbet+ and CD119+ Treg (p⩽0.05). - Conclusions - Drug-induced inhibition of Treg induction might result in low IFNy+ Treg levels with the consequence of T effector activation and impaired graft function. Further studies will show whether monitoring of IFNy+ Treg might help to prevent clinical complications provoked by an inappropriate immunosuppressive protocol.
Available online 14 November 2015
Gesehen am 06.05.2020